Central venous catheter dressing durability: an evaluation. Issue 6 (November 2015) - Richardson, Annette; Melling, Andrew; Straughan, Chris; Simms, Lisa; Coulter, Catherine; Elliot, Yvonne; Reji, Sheeja; Wilson, Natalie; Byrne, Rachael; Desmond, Catherine; Wright, Stephen E
Background: Skin organisms at the insertion site are frequently implicated in central venous catheter blood stream infections (CVC BSIs) yet few studies have compared the durability of CVC dressings in critically ill patients. Aims: To undertake an evaluation of the durability and associated costs of different CVC dressings. Methods: Dressing duration was captured prospectively using a pro forma on four different dressings on five critical care units over a 12-month period. Staff received training on CVC dressing evidence-based practices and a 'how to guide' was implemented. Findings: A total of 1229 CVC dressings were observed from 590 CVCs. One dressing had a median (IQR) duration of 68.5 h (range, 32–105 h) compared to a median duration of 43.5, 46.0 and 40.5 h for the other dressings ( P <0.001). The mean time to change a CVC dressing was 13.5 min and the cost of a dressing change was in the range of £1.97–4.97. During the 12-month study period we observed a downward trend in CVC BSIs. Discussion: Despite few dressings remaining adherent for 7 days, the low rates of CVC BSI observed suggests good dressing practices. Conclusions: One dressing appeared more durable than the others, although it was still below the recommended standard and more expensive.